Policy Review of Health Services for Abandoned Children Without National Identification Number (NIK) Under BPJS Health System - Puspita, Irma Yudith Ayu; Mulyati, Susi; Mahanani, Dian (Journal of Health Empowerment and Interprofessional Practice, 2026)
Background of study: This study examines the legal and administrative challenges faced by hospitals in providing BPJS Health services to abandoned children without a National Identification Number (NIK) in Indonesia. Despite constitutional guarantees of healthcare for all citizens, the absence of explicit regulatory mechanisms for patients without formal identification creates significant financial and operational risks for healthcare providers.Aims and scope of paper: The research aims to analyze the policy gaps in the BPJS Health system regarding coverage for abandoned children without NIK and to assess the resulting implications for hospital operations and health equity. It focuses on evaluating existing regulations and their implementation through a health policy framework.Methods: A qualitative policy analysis was conducted using Walt & Gilson's Policy Triangle framework (context, process, actors, content) and the concept of health equity. Data were collected through a comprehensive review of legal documents, government regulations, academic literature, and reports on BPJS claim processesResult: The analysis reveals significant regulatory gaps, as current policies do not explicitly include abandoned children without NIK as eligible beneficiaries. Hospitals face substantial administrative barriers, with 61.39% of claim delays attributed to incomplete documentation. Services for these children are often categorized as unfunded emergency or social care, creating financial strain on healthcare facilities and inconsistent access for vulnerable populations.Conclusion: The study concludes that clear legal instruments and standardized operational procedures are urgently needed to protect hospitals, ensure transparent claim mechanisms, and guarantee equitable healthcare access for abandoned children without NIK. Policy reforms should address both administrative requirements and systemic coordination among stakeholders to achieve true universal health coverage.